(3GdJMdjd GdGbJUGOj GdLRFj (B:s (3eOYeG H(B75 (3JeQjfG heSGdI eMdhdI (B-(3h(B65 (3JeQjfG heSGdI ebJQMI ddMd (B/s - (3aQMj, eMeOs ((3GdLRGFQ(B: s (3OGQ GSGeI(B, s, 2007)
(3GdJMdjd GdGbJUGOj dSdhc GdeSJgdc, GdJMdjd GdGbJUGOj dSdhc GdeDSSI GdefJLI, OQGSI GdGShGb hJMOjO GdGSYGQ, JeGQjf fehPLjIs
(3HHdjhZQGajG(B: (3U(B.496-498s
Keywords: (3GdEbJUGO GdJMdjdjs; (3GdEbJUGO GdLRFjs